The manipulation of odor availability of training aids used in detection canine training - Sloan, Katylynn B.; Maughan, Michele N.; Sharpes, Caitlin E.; Greubel, Robin R.; Gallegos, Shawna F.; Miklos, Aleksandr E.; Waldrop, Lindsay D. (Frontiers in Allergy, 2025)
Detection canines can identify numerous substances for which they have been trained. Historically, and a point of ongoing contention, detection canine threshold (i.e., sensitivity or limit of detection) training has primarily focused on changing the weight of the training aid substance used. There has been minimal focus on other principles, such as surface area, confinement, and temperature, which can be manipulated to affect odor availability. That said, trainers have been manipulating odor availability for years without necessarily understanding the governing scientific principles. The aim of this review is to highlight the principles that control odor availability of a substance and how an end user can apply these principles for operational detection canine training needs.